Recuperação de áreas degradadas: aplicação de metodologias socioambientais para o controle de erosão linear em propriedade rural no município de Estrela do Norte-SP - Lima, Letícia Fernanda de [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
The interventions in the environment have gained significant forces in recent centuries, especially when we consider the occurrence of the Industrial Revolution as a historical landmark, which in turn impacted the transformations of various sectors, one of them being the Environmental issues. Brazil presents in its history the great exploitation of its natural resources, making it totally geared to the capitalist market, these degradation in the landscape mainly caused by society, interfere drastically in the natural evolution of the environments. Thus, the soil as a finite natural resource is one of the natural assets that is most impacted by inadequate human practices, in this sense, the present work sought to discuss the relationship society-nature through the erosive processes, identified in a Spatial cutout, located in the rural area of the city of Estrela do Norte- SP. The aim was to contribute to the reduction of the kinetic force of rainwater through the runoff and to value the socio-environmental aspects in the field. Regarding the procedures, three soil samples were collected for textural analysis in the laboratory of Sedimentology and soil analysis of FCT/UNESP, according to the Embrapa's soil analysis Methods Manual (1997). In the analysis of the results in accordance with the proposed objectives, we sought to present the efficiency of the bioengineering technique, as regards the containment/bus of the sediments brought by rainwater. Thus, the monitoring of the buses occurred over 3 months, showing their efficiency in sediment containment, as well as in the growth of the vegetation cover...

As intervenções no meio ambiente ganharam forças significativas nos últimos séculos, sobretudo quando consideramos a ocorrência da Revolução Industrial como marco histórico, que por sua vez impactou nas transformações de diversos setores, sendo um deles as questões ambientais. O Brasil apresenta na sua história a grande exploração dos seus recursos naturais, tornando-o totalmente voltado ao mercado capitalista, essas degradações na paisagem ocasionadas principalmente pela sociedade, interferem drasticamente na evolução natural dos ambientes. Mediante a isso, o solo como recurso natural finito é um dos bens naturais que mais é impactado com as inadequadas práticas humanas, neste sentido, o presente trabalho buscou discutir a relação Sociedade-Natureza através dos processos erosivos, identificados em um recorte espacial, localizado na zona rural do município do município Estrela do Norte-SP. No caso do Pontal do Paranapanema, Oeste Paulista, o solo passou/passa por intensos processos erosivos em virtude da atividade agropecuária predominante nesta região, o que o torna altamente suscetível à ocorrências das erosões. Deste modo verificou-se a necessidade da adoção de técnicas (práticas conservacionistas) que possibilitassem a recuperação ou minimização destes impactos. Portanto, este trabalho teve como objetivo principal a implementação de técnicas de Bioengenharia com base na montagem de paliçadas e sacarias, para o controle de processos erosivos lineares (sulcos e voçorocas) identificadas em propriedade rural no município de Estrela do Norte-SP...
Keywords: Geografia; Degradação ambiental - Estrela do Norte (SP); Erosão - Estrela do Norte (SP); Bioengenharia; Geografia ambiental; Geography